Gambaran Pola Luka Luar Korban Mati Usia Dewasa Akibat Penganiayaan di RS. Bhayangkara TK. II Sartika Asih Tahun 2022 – 2024 - Sadad Afy; Andri Rusman; Dewi Handayani (Indonesian Journal Publisher, 2026)
Assault is an intentional act that may result in injury or death and remains a significant global public health issue. This study aimed to describe the characteristics and patterns of external injuries among deceased adult victims of assault at Bhayangkara Hospital Level II Sartika Asih Bandung during 2022–2024. This research used a descriptive retrospective design based on secondary data from Visum et Repertum and medical records. A total of 100 samples meeting inclusion criteria (aged 18–59 years) were analyzed using univariate methods. The results showed that most victims were aged 18–44 years (81%) and predominantly male (79%). The majority of victims were employed (58%). Most cases underwent advanced forensic examination (PLPD) (94%). Regarding injury patterns, the most common number of external injuries was two injuries (49%), followed by three injuries (29%). Among cases with a single injury, stab wounds were the most frequent (35.29%), followed by contusions (29.41%). In cases with two injuries, the most common combination was contusion and abrasion (30.6%). In conclusion, fatal assault cases predominantly affect productive-age males and commonly involve multiple external injuries, with sharp-force trauma playing a significant role. These findings provide important forensic and public health insights for violence prevention strategies.